A cross-lagged study of psychosocial adaptation among students with visual impairments: Coping, self-esteem, and social integration. (September 2022) - Xie, Zhengli; Yuan, Wei; Zhang, Li-fang
Abstract: Background: As three key indicators of psychosocial adaptation, coping, self-esteem, and social integration are vital for students with visual impairments. Aims: This study aimed to examine the reciprocal relationships among visually impaired students' coping, self-esteem, and social integration. Methods: Students with visual impairments ( N Time1 = 311, N Time2 = 170) from four special schools in mainland China responded to three inventories at two timepoints over one year. Cross-lagged panel modelling was performed to analyse the data. Results: After controlling for gender, self-esteem positively predicted self-directed coping and negatively predicted relinquished-control coping. An inverse path was found in the prediction of relinquished-control coping to self-esteem. Social integration positively predicted self-esteem. Furthermore, gender did not moderate the relationships in the cross-lagged model. Conclusions and implications: Evidence is provided for a negative loop between self-esteem and relinquished-control coping. Social integration could be a precursor of self-esteem, and self-esteem could be a precursor of self-directed coping. Moreover, the study has practical implications for special schools, teachers, parents, and students on enhancing visually impaired students' psychosocial adaptation. Highlights: Cross-lagged panel model was run among coping, self-esteem, and social integration. Negative loop was found between self-esteem and relinquished-control coping. Social integration positively predicted visually impaired students' self-esteem. Visually impaired students' self-esteem positively predicted self-directed coping.